Critical realism, post-positivism, and the possibility of knowledge - Groff, Ruth, 1963- (Routledge studies in critical realism, 2004)
Groff defends 'realism about causality' through close discussions of Kant, Hilary Putnam, Brian Ellis and Charles Taylor, among others.